PENGARUH KOMPETENSI DAN INDEPENDENSI AUDITOR TERHADAP KUALITAS AUDIT - Ririn Arianti (Media Riset Akuntansi, Auditing & Informasi, 2010)
The purpose of this study to determinde the effect of competence and independence on audit quality. The variables which used in this research are competence and independence as a independent variable, and audit quality as a dependent variable. Competence is measured by knowledge, experience, and formal education, while independence is measured by auditor tenure, pressure from clients, peer review and nonaudit services. The results show that competence significantly influence on audit quality but independence has not significant influence on audit quality.Key words: Competence, Independence and Audit Quality